Relationship banking: does it lower information asymmetry or increase lender monopoly power? - Lucente, Luiz Armando (2014)
The theoretical literature regarding banking economics indicates that long-term relationships between a lender and a borrower can reveal information about the firm’s credit rating. Nonetheless, theoretical studies foresee different results from the effect of banking relationship regarding interest rates and the quantity of capital offered to a firm. According to Diamond (1991) and others, if the banking relationship reveals to all creditors the quality of the firm’s credit, therefore effects such as the increase in the loan amount available to the firm and interest rate reduction are expected. On the other hand, if banking relationship only reveals the firm’s credit information to the main supplier, then it could not have the effect from the increased lending amount and interest rate reduction. This paper demonstrates empirically what are effects from public and private information generated by banking relationship in the total quantity of capital (loan) offered to the firm and interest rate charged by financial institutions. We used the length of the relationship between the lender and the borrower as a measure, since it can be found in external bureaus such as Serasa Experian and SCPC (Credit Reporting Agency) or at SISBACEN (Central Bank Information System). We used as private information model measures that indicate late payments of debts from the borrower, which are known exclusively by each creditor. According to the theory, it is expected that public information related to length of the relationship with the bank will result in higher loan amount availability and lower interest rates. Private information regarding late payments will not have effect over the loan amount availability and interest rate, since they are exclusive information from the main creditor. In the empiric test, more than two thousand six hundred and eighty five loans related to working capital products granted to fifty-three companies lent by a financial institution in the state of Espírito Santo, were analyzed. Using the panel data with fixed firm effect econometric model, we found that the length of the relationship with the bank is positively correlated to the availability of capital to a firm and negatively correlated to the banking spread. Both effects are statistically significant at 5.00% level. Similar to the results found by Berger and Udell (1995). The results show that a long-term relationship between firms and financial institutions reduce the information asymmetry, generating benefits for the firms. In order to test the private information effect, we used information of defaults from the firms with the financial institution. Those data were used internally, not disclosed to credit bureaus. The variables tested were number of outstanding installments in the previous month, the sum of outstanding installments, flag in case the late payments had already been made and months since the last late payment. There are no effects of private information on spread and the total availability of capital. Similar to the results found by Sharpe (1990).